PENGARUH MANAJEMEN FUNDRAISING DAN KUALITAS PELAYANAN TERHADAP KEPERCAYAAN MUZAKKI PADA WAHDAH INSPIRASI ZAKAT CABANG KALIMANTAN TIMUR - Riyani Riyani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine the effect of fundraising management and service quality on muzakki trust. This research was conducted at Wahdah Inspirasi Zakat (WIZ) East Kalimantan branch with a total sample of 92 respondents. Collecting data in this study using a questionnaire distributed to respondents. The results showed that 92 respondents obtained a correlation coefficient (R) of 0.766, which means that the relationship between the independent variable and the dependent variable is strong. The coefficient of determination (R2) obtained is 0.586 or 58.6%, which means that the influence of fundraising management variables and service quality is 58.6% on Muzakki's trust and 41.4% is influenced by other variables. The F test obtained is very significant, the effect of fundraising management and service quality on muzakki's trust is 63,116> 3,10, there is a simultaneous significant effect on muzakki's trust. The t test (partial) on the fundraising management variable on Muzakki's trust was 1.307 <1.986, which means that fundraising management did not have a significant effect on Muzakki's trust, while the t (partial) test on the variable service quality on Muzakki's trust was 8.387 <1.986 which This means that the quality of service has a significant effect on Muzakki's trust.